Metabolic flux towards the (iso)flavonoid pathway in lignin modified alfalfa lines induces resistance against Fusarium oxysporum f. sp. medicaginis. (21st November 2017) - Gill, Upinder S.; Uppalapati, Srinivasa R.; Gallego‐Giraldo, Lina; Ishiga, Yasuhiro; Dixon, Richard A.; Mysore, Kirankumar S.
Abstract: Downregulation of lignin in alfalfa ( Medicago sativa L.) is associated with increased availability of cell wall polysaccharides in plant cells. We tested transgenic alfalfa plants downregulated for Caffeoyl‐CoA O‐methyltransferase ( CCoAOMT ) against an economically important fungal disease of alfalfa, Fusarium wilt caused by Fusarium oxysporum f. sp. medicaginis, and found it more resistant to this disease. Transcriptomic and metabolomic analyses indicated that the improved disease resistance against Fusarium wilt is due to increased accumulation and/or spillover of flux towards the (iso)flavonoid pathway. Some (iso)flavonoids and their pathway intermediate compounds showed strong accumulation in CCoAOMT downregulated plants after F. oxysporum f. sp. medicaginis inoculation. The identified (iso)flavonoids, including medicarpin and 7, 4′‐dihydroxyflavone, inhibited the in vitro growth of F. oxysporum f. sp. medicaginis . These results suggested that the increased accumulation and/or shift/spillover of flux towards the (iso)flavonoid pathway in CCoAOMT downregulated plants is associated with induced disease resistance. Abstract : Lignin modification in plants benefits biofuel, pulping, and forage industries through improving the accessibility of cell wall polysaccharides to chemical, microbial, or enzymatic digestion. Here, we found that the alfalfa lines downregulated for lignin content are also resistant to Fusarium wilt. We found that improved resistance is associated with a metabolic flux shift towards the (iso)flavonoid pathway with increased accumulation of (iso)flavones such as medicarpin and 7, 4′‐dihydroxyflavone in roots that inhibited growth of the fungal pathogen, Fusarium oxysporum f. sp. medicaginis the causal agent of Fusarium wilt.